2008
DOI: 10.1681/asn.2007040419
|View full text |Cite
|
Sign up to set email alerts
|

HIF Activation Protects From Acute Kidney Injury

Abstract: The contribution of hypoxia to cisplatin-induced renal tubular injury is controversial. Because the hypoxia-inducible factor (HIF) pathway is a master regulator of adaptation to hypoxia, we measured the effects of cisplatin on HIF accumulation in vitro and in vivo, and tested whether hypoxic preconditioning is protective against cisplatin-induced injury. We found that cisplatin did not stabilize HIF-1␣ protein in vitro or in vivo under normoxic conditions. However, hypoxic preconditioning of cisplatin-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
126
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 165 publications
(133 citation statements)
references
References 44 publications
5
126
1
1
Order By: Relevance
“…This study demonstrates that (1) targeted deletion of Vhl in the TAL associated with increased HIF-mediated gene transcription conveys substantial protection against ischemic injury and that (2) protection of this comparatively small nephron segment translates into a marked preservation of whole kidney function. Although these findings complement previous data showing that systemic and nonselective cellular stabilization of HIF protects against ischemic 29,31 and toxic renal injury, 28,30 this study extends these results by demonstrating that Vhl deletion in a specific nephron segment is sufficient to achieve renal protection. Moreover, in contrast to previously published mice with cell type specific inactivation of Vhl, 32 the phenotype of animals with Vhl deletion in TALs was surprisingly normal, indicating that Vhl pathology is context-dependent.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study demonstrates that (1) targeted deletion of Vhl in the TAL associated with increased HIF-mediated gene transcription conveys substantial protection against ischemic injury and that (2) protection of this comparatively small nephron segment translates into a marked preservation of whole kidney function. Although these findings complement previous data showing that systemic and nonselective cellular stabilization of HIF protects against ischemic 29,31 and toxic renal injury, 28,30 this study extends these results by demonstrating that Vhl deletion in a specific nephron segment is sufficient to achieve renal protection. Moreover, in contrast to previously published mice with cell type specific inactivation of Vhl, 32 the phenotype of animals with Vhl deletion in TALs was surprisingly normal, indicating that Vhl pathology is context-dependent.…”
Section: Discussionsupporting
confidence: 89%
“…25,26 Previous studies have shown that systemic hypoxia or pharmacologic approaches to stabilize HIF can protect the kidney against subsequent ischemic or toxic injury. [27][28][29][30][31] In addition, Vhl knockout strategies have been successfully applied to stabilize HIF genetically 32 and acute ubiquitous inactivation of Vhl has recently been shown to ameliorate ischemic AKI. 33 All of these approaches have so far not allowed defining the role of specific parts of the nephron in AKI protection.…”
mentioning
confidence: 99%
“…With the in vivo administration of cobalt to activate HIF, the number of apoptotic renal tubular cells became much smaller in cisplatin nephropathy [23]. Furthermore, induction of HIF with carbon monoxide before exposure of cisplatin significantly reduced histological renal damage and tubular apoptosis in cisplatin nephropathy [42].…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…4a and b). Higher HIF-1a levels provide protection against cellular injuries in many tissues including lungs, 35 kidney, 36 nerves, 37 and retinal. 38 However, many cancer cells also express higher levels of HIF-1a where it stimulates angiogenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…After serum deprivation, cells were then treated with CoCl 2 (100 and 500 mM; Sigma, St. Louis, MO) in 1% FBS medium and incubated for 48 h. Conditioned medium was collected at different time points (12,24,36, and 48 h) for zymography or Western blot analysis.…”
Section: Mechanical Injurymentioning
confidence: 99%